(untitled) (IEM Journal, 2024)
Flooding is a persisting challenge in Malaysia. Combating flood risk has become a main priority for sustainable development in this country. The application of sophisticated engineering in hard structure approaches and flood control systems are often incongruous to the public. Therefore, there is a need to integrate the soft engineering approaches and the best practises of flood management to mitigate flood risk. There is also a need to integrate the concept of sustainable development into its planning policies towards flood hazard reduction. Mobile flood protection measures are useful as an alternative solution in flood protection and mitigation purposes. Mobile protective systems can be used for temporarily increasing the height of permanent flood protection structures during extreme events and can be utilised as emergency measure against flooding in unprotected low-lying areas. As the available mobile systems differ in the type of material, method of installation and available protection height, a description of their features, and potential application were examined including their respective opportunities and drawbacks. This article presents a review on different types of lightweight mobile flood wall barrier (MFWB) that were implemented to cope with floods in Malaysia with examples of application in other countries such as United Kingdom, Slovakia, and Netherlands. The MFWB products are reviewed and compared to each other according to the types, characteristics, mechanisms, drawbacks and how these measures are integrated into spatial planning. Based on the findings, several suggestions are given on how to improve the flood risk management in flood-prone areas and way forward for Malaysia.